2015
DOI: 10.3109/13880209.2014.1001408
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of kombucha on rats fed a hypercholesterolemic diet is mediated by its antioxidant activity

Abstract: Context: Kombucha (KT) is claimed to have various beneficial effects on human health, but there is very little scientific evidence available in the literature. Objective: The present study investigates the effects of Camellia sinensis (GT) Linn. (Theaceae) and KT, two natural drinks, on cholesterol and antioxidant status using a hypercholesterolemia rat model. Materials and methods: The present study compared the free-radical scavenging abilities and polyphenol levels of GT and KT. Wistar rats fed cholesterol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 54 publications
7
30
1
4
Order By: Relevance
“…Another study of mung beans showed a reduction in the concentrations of AST and ALT in animals treated with aqueous extract of fermented and germinated mung beans, rich in antioxidant compounds, in a model of alcohol-induced hepatic steatosis, compared to untreated animals [ 40 ]. Similarly, Bellassoued et al [ 41 ] found lower concentrations of these enzymes in rats fed hypercholesterolemic diets when they were treated with fermented green tea (konbucha) as compared with untreated animals. These authors attributed this protective effect to the antioxidant potential of fermented green tea.…”
Section: Resultsmentioning
confidence: 98%
“…Another study of mung beans showed a reduction in the concentrations of AST and ALT in animals treated with aqueous extract of fermented and germinated mung beans, rich in antioxidant compounds, in a model of alcohol-induced hepatic steatosis, compared to untreated animals [ 40 ]. Similarly, Bellassoued et al [ 41 ] found lower concentrations of these enzymes in rats fed hypercholesterolemic diets when they were treated with fermented green tea (konbucha) as compared with untreated animals. These authors attributed this protective effect to the antioxidant potential of fermented green tea.…”
Section: Resultsmentioning
confidence: 98%
“…And recently, Bellassoued et al. () worked with rats fed with cholesterol‐rich diets and high thiobarbituric acid reactive substances (TBARS) levels, and found that the TBARS concentration was significantly reduced in the liver and kidney after the treatment with the fermented tea. Their results showed that Kombucha tea could be considered as a therapeutic agent against liver and kidney toxicities.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Bellassoued et al. () demonstrated that the high TBARS concentration was significantly reduced in the liver and kidney of rats fed with cholesterol‐rich diets after the treatment with fermented tea (Bellassoued et al., ). The antitoxigenic effect of kombucha has been attributed to its antioxidant activity and the hepatoprotective effects against acetaminophen were primarily attributed to the presence of DSL (Wang et al., ).…”
Section: Beneficial Effects Of Aab‐fermented Productsmentioning
confidence: 99%
“…Investigations in cell lines animal models found that kombucha can protect against hepatotoxicity caused by several toxicants such as paracetamol, carbon-tetrachloride, aflatoxin B1, and acetaminophen (Jayabalan, Baskaran, Marimuthu, Swaminathan, & Yun, 2010;Pauline et al, 2001;Wang et al, 2014). Bellassoued et al (2015) demonstrated that the high TBARS concentration was significantly reduced in the liver and kidney of rats fed with cholesterol-rich diets after the treatment with fermented tea (Bellassoued et al, 2015). The antitoxigenic effect of kombucha has been attributed to its antioxidant activity and the hepatoprotective effects against acetaminophen were primarily attributed to the presence of DSL (Wang et al, 2014).…”
Section: Health Benefits Associated With Kombuchamentioning
confidence: 99%